Highly ferromagnetic, transparent conducting electrode based on Ce1−xCuxO2 thin film for spintronic applications. Issue 7 (August 2015) - Mahmoud, Waleed E.; Al-Ghamdi, A.A.; Al-Agel, F.A.; Al-Arfaj, E.; Shokr, F.S.; Al-Gahtany, S.A.; Alshahrie, Ahmed; Shirbeeny, W.; Bronstein, L.M.; Beall, Gary W.
Abstract: Here, we report, for the first time, syntheses of ferromagnetic transparent conducting electrodes based on Ce1− x Cu x O2 (0.01< x <0.17). These electrodes were synthesized using an ethylene glycol modified sol–gel spin coating technique. To assess the properties of the transparent conducting electrodes, we studied the influence of the amount of the Cu dopant on the structural, optical, electrical and magnetic properties of the CeO2 films. The films were characterized using X-ray powder diffraction, scanning electron microscopy combined with energy dispersive spectroscopy, atomic force microscopy, electrical and magnetic measurements. The data obtained demonstrate that the structure and composition govern the performance characteristics of these films as transparent electrodes. An efficient ferromagnetic transparent conducting electrode with the high transparency (87%), low sheet resistance (0.8 Ω/cm 2 ) and the high magnetic moment (1.63 µB /Cu) was obtained by doping CeO2 with 9 at% of Cu ions.